Osteosarcoma‐initiating cells show high aerobic glycolysis and attenuation of oxidative phosphorylation mediated by LIN28B. Issue 1 (29th November 2019) - Mizushima, Emi; Tsukahara, Tomohide; Emori, Makoto; Murata, Kenji; Akamatsu, Asuka; Shibayama, Yuji; Hamada, Shuto; Watanabe, Yuto; Kaya, Mitsunori; Hirohashi, Yoshihiko; Kanaseki, Takayuki; Nakatsugawa, Munehide; et al.
Abstract: Osteosarcoma (OS) is a highly malignant bone tumor and the prognosis for non‐responders to chemotherapy remains poor. Previous studies have shown that human sarcomas contain sarcoma‐initiating cells (SIC), which have the characteristics of high tumorigenesis and resistance to chemotherapy. In the present study, we characterized SIC of a novel OS cell line, screened for SIC‐related genes, and tried to regulate the proliferation of OS by metabolic interference. Initially, we established a new human OS cell line (OS13) and isolated clones showing higher tumorigenesis as SIC (OS HIGH ) and counterpart clones. OS HIGH cells showed chemoresistance and their metabolism highly depended on aerobic glycolysis and suppressed oxidative phosphorylation. Using RNA‐sequencing, we identified LIN28B as a SIC‐related gene highly expressed in OS HIGH cells. mRNA of LIN28B was expressed in sarcoma cell lines including OS13, but its expression was not detectable in normal organs other than the testis and placenta. LIN28B protein was also detected in various sarcoma tissues. Knockdown of LIN28B in OS13 cells reduced tumorigenesis, decreased chemoresistance, and reversed oxidative phosphorylation function. Combination therapy consisting of a glycolysis inhibitor and low‐dose chemotherapy had antitumor effects. In conclusion, manipulation of glycolysis combined with chemotherapy might be a good adjuvant treatment for OS. Development of immunotherapy targeting LIN28B, a so‐called cancer/testis antigen, might be a good approach. Abstract : Osteosarcoma‐initiating cell antigen LIN28B was expressed in sarcoma tissues. ES, epithelioid sarcoma; MFS, myxofibrosarcoma; OS, osteosarcoma; SS, synovial sarcoma.